2016
DOI: 10.18632/oncotarget.9375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of fluorine-18 2-fluoro-2-deoxy-D-glucose positron emission tomography/computed tomography in penile cancer

Abstract: PurposeThis study investigated the value of Fluorine-18 2-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography (PET)/computed tomography (CT) imaging in the management of patients with advanced penile cancer.Patients and MethodsBetween January 2009 and August 2012, 48 patients with penile cancer at our center underwent FDG-PET/CT after CT (n=39) or magnetic resonance imaging (MRI; n=9). The accuracy of FDG-PET/CT was assessed with both organ-based and patient-based analyses. FDG-PET/CT findings were val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The performance is better if palpably enlarged inguinal lymph nodes are present. [ 95 ] However, the evidence is insufficient and is not recommended by NCCN or ESMO as of now.…”
Section: Penile Cancermentioning
confidence: 99%
“…The performance is better if palpably enlarged inguinal lymph nodes are present. [ 95 ] However, the evidence is insufficient and is not recommended by NCCN or ESMO as of now.…”
Section: Penile Cancermentioning
confidence: 99%
“…Graafland et al evaluated 18 patients with metastatic spread to inguinal nodes and then underwent evaluation of their pelvic nodes and found a sensitivity of 91% and specificity of 100% ( 48 ). Another study of patients with advanced disease, all of whom had inguinal disease and 21/48 (43.8%) who presented with distant metastases found 18F-FDG-PET/CT to have a sensitivity and specificity of 82% and 93%, and overall was able to detect 33% more metastatic lesions than cross-sectional imaging alone ( 49 ).…”
Section: Sln Biopsymentioning
confidence: 99%
“…In stage 3 and 4 patients, Zhang et al showed good results for lymph nodes (all locations) with a sensitivity of 93% and a specificity of 85% ( 18 ). Also in other malignancies and lymph node areas, results suggest that FDG-PET/CT has higher accuracy than CT only in staging pelvic lymph nodes ( 5 , 6 , 19 , 20 ).…”
Section: Lymph Node Stagingmentioning
confidence: 99%
“…The largest series by Zhang et al [2016] compared FDG-PET/CT to conventional CT in 42 patients with suspicious lesions on CT or MRI, leading to an implicit selection bias ( 18 ). With histopathology or follow-up imaging as a reference, sensitivity and specificity of FDG-PET/CT were 85% and 86% respectively for all metastatic sites, including lymph nodes, lung, bone, etc.…”
Section: Distant Metastasesmentioning
confidence: 99%
See 1 more Smart Citation